2017
DOI: 10.1007/s00415-017-8419-x
|View full text |Cite
|
Sign up to set email alerts
|

The yield of initial conventional MRI in 115 cases of angiographically confirmed spinal vascular malformations

Abstract: MRI is the primary screening tool for patients with myelopathy. The decision to obtain additional imaging, notably spinal angiography, is generally based on initial MRI findings. This study retrospectively analyzed the yield of initial MRI in a cohort of patients with angiographically confirmed vascular malformations. MRI obtained at symptom onset was available in 115 patients with either high-flow (29 cases) or low-flow (86 cases) vascular malformations. MRI was classified as "positive" when the report mentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…3 Flow voids, however, are observed in only about 70% of cases; moreover, the detection rate could be very low (Ͻ40%) in low-flow shunt lesions. 3,14 Advanced MR images can improve the sensitivity and diagnostic accuracy for the detection of SVM. Amarourche et al 10 reported the utility of the TRCE MR imaging technique (TRICKS) in the evaluation of different types of SVMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Flow voids, however, are observed in only about 70% of cases; moreover, the detection rate could be very low (Ͻ40%) in low-flow shunt lesions. 3,14 Advanced MR images can improve the sensitivity and diagnostic accuracy for the detection of SVM. Amarourche et al 10 reported the utility of the TRCE MR imaging technique (TRICKS) in the evaluation of different types of SVMs.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,17 In our study, we found that VHHT2WI and TRCE MR imaging had high sensitivity and accuracy in the diagnosis of SVM, concurrent with other reported studies in the literature. [10][11][12][13][14][15] Although the diagnosis of SDAVF could be confidently made using either sequence, a false-positive diagnosis was a concern for both. In our series, 2 cases of PMAVF and 1 case each of PMAVF and SCAVM were erroneously diagnosed as SDAVFs.…”
Section: Discussionmentioning
confidence: 99%
“…In a large retrospective study, MRI had a sensitivity of 38% for angiographically confirmed low-flow spinal vascular lesions and 40% of cases were initially misdiagnosed as myelitis 2. Gadolinium enhancement is often interpreted to indicate acute inflammation1 but it is not specific and this may also occur in dural arteriovenous fistula due to chronic venous congestion and breakdown of the blood–spinal cord barrier.…”
Section: Discussionmentioning
confidence: 99%
“…There may be patchy intramedullary enhancement due to breakdown of the blood-cord barrier. In some cases, abnormal vasculature may be identified that may be useful to guide spinal arteriography and intervention [5,[89][90][91].…”
Section: Initial Imagingmentioning
confidence: 99%
“…A variety of cysts and benign neoplasms can also compress the cord; they tend to arise within the intradural compartment. The most common of these are nerve sheath tumors, meningiomas, and arachnoid adhesions/cysts [4][5][6][7][8][9][10].…”
Section: Summary Of Literature Review Introduction/backgroundmentioning
confidence: 99%